If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7 = 10y Reorder the terms: 7 + 3x = 10y Solving 7 + 3x = 10y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3x = -7 + 10y Combine like terms: 7 + -7 = 0 0 + 3x = -7 + 10y 3x = -7 + 10y Divide each side by '3'. x = -2.333333333 + 3.333333333y Simplifying x = -2.333333333 + 3.333333333y
| x^3-3x^2-16x-12=0 | | 3[3-(-6x-7)]=90x+114 | | x+83= | | 2(x-4.40)=6.60 | | 3(t+1)=5(2t-5) | | 3x^2+3y^2-15x-30y=0 | | (2x^2-7)(8x^2+3)= | | 4y-16+8y=-4y | | 7(5x+2)=x+3 | | 4w+8= | | 4mn+3m+8n+6= | | 5w+5= | | 8x+9-4(x+1)=9x+7 | | 3p+80=-2p | | 3640=P(l+0.06*5) | | 8Y+9X=73.50 | | (3x+8)(6+x)=0 | | 4(3t+1)-7=t-(t+2) | | m-17/5-7m-7/4=3 | | 6-6(3x-4)=12 | | 3p-15=6p | | 2.4x+34.4=2.9-8.1x | | 25x^2-85x+81=0 | | x+x*0.07=100 | | x-401.94=144.23 | | 3y+9=2y-7 | | k=5x^6 | | 6x+7=4x+31 | | 4p+14=-14 | | x+62=223 | | (6a^4+2a+6-a^2)-(7a-6a^3+3a^2-5a-6a-6)= | | 7x+5=4x+44 |